Risk Management In The Operation Of Automatic Teller Machines Case Study Of Bank Syariah Indonesia Medan - Ritonga, Ali Mahadi; Sugianto, Sugianto; Syakir, Ahmad (JURNAL MANAJEMEN PENDIDIKAN, 2025)
The purpose of this study is to analyze risk management in the operation of Automatic Teller Machine (ATM) at PT. Bank Syariah Indonesia. This study uses a descriptive qualitative method to test data through interviews. The results of this study show risk management in the management of Automatic Teller Machine (ATM). ATM operational risk management at BSI has been running with various security systems, but it still needs improvement, especially in terms of security risk mitigation, operational optimization, and customer education. With the strengthening of a more proactive strategy and the use of advanced technology, the effectiveness of ATM risk management at BSI can be further improved.